Розвиток науково-дослідницьких послуг в умовах глобалізаційних викликів перед освітніми установами України і Швейцарії - Мартинюк, Христина Андріївна; Martyniuk, Khrystyna Andriivna (Національний університет "Львівська політехніка", 2024)
Розвиток науково-дослідницьких послуг в умовах глобалізації характеризується системними трансформаціями, що охоплюють технологічні, економічні, соціальні та інституційні аспекти. Глобалізаційні процеси створюють принципово нове середовище для наукової діяльності, яке вимагає від освітніх установ постійної адаптації, впровадження інноваційних підходів та готовності до міжнародної колаборації. Об’єктом даного дослідження виступає Національний університет «Львівська політехніка», а саме кафедра менеджменту і міжнародного підприємництва, яка надає широкий спектр освітніх та науково-дослідницьких послуг. Предметом дослідження є даної магістерської кваліфікаційної роботи є розвиток науково-дослідницьких послуг в умовах глобалізаційних викликів перед освітніми установами України і Швейцарії Метою магістерської кваліфікаційної роботи є аналіз сучасних тенденцій розвитку науково-дослідних послуг в умовах глобалізаційних викликів, аналізу стану фінансово-господарської діяльності Національного університету «Львівська політехніка» та розробці рекомендацій щодо підвищення ефективності їх впровадження в освітніх установах. Для реалізації поставленої мети заплановано виконати такі завдання, як проаналізувати нормативно-правову базу щодо розвитку науково-дослідницьких послуг, визначити сутність та особливості науково-дослідницьких послуг в освітніх установах; розглянути основні виклики науково-дослідницьких послуг в освітніх установах; дослідити сучасні тенденції, інновації та можливості для застосування цифрових технологій у сфері наукових досліджень, що впливають на розвиток освітніх установ; оцінити ефективність міжнародної співпраці в контексті наукових досліджень освітніх установ між Україною та Швейцарією; здійснити аналіз фінансово-економічної діяльності Національного університету «Львівська політехніка»; розробити рекомендації щодо удосконалення науково-дослідницьких послуг освітніх установ у контексті глобалізаційних викликів. Науково-дослідницькі послуги в освітніх установах - це діяльність, спрямована на виконання досліджень, розробок та інноваційних проєктів у різних галузях науки, техніки, технологій, гуманітарних і соціальних наук. Їх сутність полягає в сприянні генерації нових знань, практичних рішень та технологій, які мають теоретичну та прикладну цінність. Дані послуги в освітніх установах є важливим компонентом, який поєднує такі діяльності, як освітню, наукову та інноваційну. Вони передбачають проведення досліджень, створення нових знань, розробку інноваційних технологій, а також забезпечення умов для реалізації наукового потенціалу студентів і викладачів [1-5]. В рамках дослідження було обґрунтовано впровадження Research Flow підходу у рамках діяльності кафедри менеджменту і міжнародного підприємництва дозволить створити сприятливу інфраструктуру для ефективного управління науково-дослідницькими проектами, забезпечити кращу комунікацію між науковими групами та бізнесом, а також активніше залучати міжнародні гранти та партнерства. Такий підхід дозволяє досягти високої продуктивності досліджень та їх комерціалізації, що є важливим для підвищення науково-технічного потенціалу України на міжнародній арені. Впровадження даного заходу дозволяє оцінити ключові фінансово-економічні показники.

The development of research services in the context of globalization is characterized by systemic transformations that encompass technological, economic, social and institutional aspects. Globalization processes create a fundamentally new environment for scientific activity, which requires educational institutions to constantly adapt, implement innovative approaches and be ready for international collaboration. The object of this study is the Lviv Polytechnic National University, namely the Department of Management and International Entrepreneurship, which provides a wide range of educational and research services. The subject of this master's qualification work is the development of scientific and research services in the context of globalization challenges facing educational institutions in Ukraine and Switzerland. The purpose of the master's qualification work is to analyze current trends in the development of scientific and research services in the context of globalization challenges, analyze the state of financial and economic activities of the National University "Lviv Polytechnic" and develop recommendations for increasing the effectiveness of their implementation in educational institutions. To achieve the goal, it is planned to perform the following tasks: analyze the regulatory framework for the development of research services, determine the essence and features of research services in educational institutions; consider the main challenges of research services in educational institutions; investigate current trends, innovations and opportunities for the application of digital technologies in the field of scientific research that affect the development of educational institutions; assess the effectiveness of international cooperation in the context of scientific research of educational institutions between Ukraine and Switzerland; analyze the financial and economic activities of the National University "Lviv Polytechnic"; develop recommendations for improving research services of educational institutions in the context of globalization challenges. Research services in educational institutions are activities aimed at carrying out research, development and innovative projects in various fields of science, engineering, technology, humanities and social sciences. Their essence is to promote the generation of new knowledge, practical solutions and technologies that have theoretical and applied value. These services in educational institutions are an important component that combines such activities as educational, scientific and innovative. They involve conducting research, creating new knowledge, developing innovative technologies, as well as providing conditions for the realization of the scientific potential of students and teachers [1-5]. The study substantiated the implementation of the Research Flow approach within the framework of the activities of the Department of Management and International Entrepreneurship, which will create a favorable infrastructure for the effective management of research projects, ensure better communication between scientific groups and business, as well as more actively attract international grants and partnerships. This approach allows achieving high productivity of research and its commercialization, which is important for increasing the scientific and technical potential of Ukraine in the international arena. The implementation of this measure allows assessing key financial and economic indicators.
Development of scientific and research services under the conditions of globalization challenges for educational institutions of Ukraine and Switzerland
Keywords: 8.292.00.01; розвиток; послуги; наука; глобалізація; освітні установи; науково-дослідницькі; development; services; science; globalization; educational institutions; research List of used literature sources: 1. Gudz; Yu. and Atamanska; S.; 2024. Features of commercialization of research results in modern conditions. Modernization of higher education and ensuring the quality of educational activities in the context of European integration: materials of the International Scientific and Methodological Conference. conference; Kharkiv; Ukraine; October 18; 2024. Kharkiv: DBTU 2. Isakova N.B.; Goncharova T.V.; 2024. Development of Ukrainian universities in the context of some modern world trends. Science and science; No. 3 (125). pp. 43-67. https://doi.org/10.15407/sofs2024.03.043 3. Tarasenko; O.S.; 2024. Modeling the relationship between the demand for educational services and the position of the institution in the Webometrics Ranking of World Universities. Journal of Strategic Economic Research; (1); pp. 8–20. https://doi.org/10.30857/2786-5398.2024.1.1 4. Ryzhko; L.; Bessalova; T. and Zhivaga; O.; 2024. Program-targeted scientific research. Methodology. Praxeology: monograph. Kyiv: Yarochenko Ya.V. 5. Furmanenko; I.; 2024. Proposals for improving the methods of promoting educational services of a higher education institution. In: O. Patryak et al.; ed.; World of Scientific Research. Issue 27: materials of the International Multidisciplinary Scientific Internet Conference. Ternopil; Ukraine; Opole; Poland; February 22-23; 2024. Ternopil: FO-P Shpak V.B